1978
DOI: 10.1111/j.1365-2362.1978.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic acetylation and aminopyrine demethylation in Gilbert's syndrome

Abstract: Polymorphic acetylation was investigated in twenty-seven patients with Gilbert's syndrome using the sulphadimidine test. Whereas the finding of 51% slow acetylators in seventy-eight control persons agreed well with the expected frequency in a continental European population, the prevalence of slow acetylators in Gilbert's syndrome was increased to 78% (P less than 0.03, Woolf's G-test). After oral administration of 14C-aminopyrine there was no significant difference between seventeen patients with Gilbert's sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our results, with a greater number of patients, confirm the findings of Platzer et al (1978). 74.1% of the patients with Gilbert's syndrome were SA compared with 54.7% of the healthy volunteers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results, with a greater number of patients, confirm the findings of Platzer et al (1978). 74.1% of the patients with Gilbert's syndrome were SA compared with 54.7% of the healthy volunteers.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study suggested that the slow acetylator phenotype is more prevalent among individuals with Gilbert's syndrome (Platzer et al, 1978). These authors also reported lower plasma concentrations of AcSM at 6 h after SM administration and speculated on the absence of homozygous rapid genotypes in Gilbert's syndrome.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to increased adverse reactions in slow acetylators treated with drugs whose elimination is primarily determined by acetylation, there are a number of associations of the acetylator phenotype with drug-induced and spontaneous disease. However, apart from the increased incidence of bladder cancer in the slow-acetylator phenotype (7)-carcinogenic amines causing bladder cancer are substrates for NAT-the associations of polymorphic acetylation with Gilbert disease (8), advanced breast cancer (9), diabetes (10), and leprosy (11) remain mechanistically unexplained.…”
mentioning
confidence: 99%